ANALYSIS OF THE CAUSES OF EARLY MARRIAGE (CASE STUDY IN PENYAMUN VILLAGE, PEMALI DISTRICT IN 2024) - Purnamasari, Wulan; Jonimar, Jonimar; Kurrohman, Taufik (HEARTY, 2025)
According to Indonesia's Central Statistics Agency, the rate of early marriage in Bangka Belitung increased sharply from 14.22% in 2018, to 15.48% in 2019, and reached 18.78% in 2020, making it the highest in Indonesia. Based on a May 2024 survey in Penyamun Village, Pemali District, early marriage in this area is generally triggered by promiscuity that causes pregnancy out of wedlock. As a result, many teenagers are married in series by their parents. This study aims to analyze the causes of early marriage in Penyamun Village with qualitative methods and phenomenological approaches. The findings of the study show that the attitude and relationship of parents that are not harmonious and indifference to children are the main factors. Teens who feel less attention from their parents often seek attention from male friends, potentially leading to pregnancy out of wedlock. In addition, the surrounding environment that does not support higher education and early marriage is considered a solution for adolescents who get pregnant out of wedlock. This condition is exacerbated by parents who choose to marry their children to avoid social stigma. Overall, factors such as disharmonious parental relationships, social environmental patterns, and out-of-wedlock pregnancies contributed significantly to the high rate of early marriage in Penyamun Village